The Influence Of Nutrition Counseling On The Knowledge And Intake Of Macro Nutrient Wus Kek In Region Work Puskesmas Sawah Lebar Bengkulu - Meili Dwi Ananda; Jumiyati Jumiyati; Emy Yuliantini (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2019)
Women of Childbearing Age (WUS) are a population that are of particular interest inthe prevention of nutritional problems, especially in addressing their Lack of Chronic Energy (KEK). KEK in WUS is very likely to result in a difficult childbirth and post partum hemorrhage as well as an increased risk death of the mother and of low birth weight babies. Data WUS SEZ in Indonesia in 2010 (30,9%) increased in 2013 (46,4%). Sixteen provinces with the prevalence of the risk of SEZ above the national province, namely the Bengkulu Province (15%). The purpose of this study is to determine the effect of nutrition counseling on the knowledge and intake of macro nutrient on WUS SEZ in the working area of Health Center of Sawah Lebar the Width of the City of Bengkulu the Year 2018. The results of this study there was significant influence of nutritional counseling (p = 0.000) on the intake of macro nutrient (p = 0.000). On WUS KEK in the working area of Health Center of Sawah Lebar the width of the city of bengkulu the year 2018.The Design of this Research is Pre Experimental Design with design One Group Pretest-Posttest. Nutrition counseling on WUS KEK performed 3 times during 3 weeks. The number of samples as many as 23 people. Statistical analysis using dependent t-test and wilcoxon test